Molecular characterization of a class I P450 electron transfer system from Novosphingobium aromaticivorans DSM12444. - Yang, W; Bell, S; Wang, H; Zhou, W; Hoskins, N; Dale, A; Bartlam, M; Wong, L; Rao, Z (2010)
Cytochrome P450 (CYP) enzymes of the CYP101 and CYP111 families from the oligotrophic bacterium Novosphingobium aromaticivorans DSM12444 are heme monooxygenases that receive electrons from NADH via Arx, a [2Fe-2S] ferredoxin, and ArR, a ferredoxin reductase. These systems show fast NADH turnovers (k(cat) = 39-91 s(-1)) that are efficiently coupled to product formation. The three-dimensional structures of ArR, Arx, and CYP101D1, which form a physiological class I P450 electron transfer chain, have been resolved by x-ray crystallography. The general structural features of these proteins are similar to their counterparts in other class I systems such as putidaredoxin reductase (PdR), putidaredoxin (Pdx), and CYP101A1 of the camphor hydroxylase system from Pseudomonas putida, and adrenodoxin (Adx) of the mitochondrial steroidogenic CYP11 and CYP24A1 systems. However, significant differences in the proposed protein-protein interaction surfaces of the ferredoxin reductase, ferredoxin, and P450 enzyme are found. There are regions of positive charge on the likely interaction face of ArR and CYP101D1 and a corresponding negatively charged area on the surface of Arx. The [2Fe-2S] cluster binding loop in Arx also has a neutral, hydrophobic patch on the surface. These surface characteristics are more in common with those of Adx than Pdx. The observed structural features are consistent with the ionic strength dependence of the activity.